Combining PD-1/PD-L1 blockade with type I interferon in cancer therapy - Razaghi, Ali; Durand-Dubief, Mickaël; Brusselaers, Nele; Björnstedt, Mikael (Frontiers in Immunology, 2023)
PD-1 and PD-L1 are crucial regulators of immunity expressed on the surface of T cells and tumour cells, respectively. Cancer cells frequently use PD-1/PD-L1 to evade immune detection; hence, blocking them exposes tumours to be attacked by activated T cells. The synergy of PD-1/PD-L1 blockade with type I interferon (IFN) can improve cancer treatment efficacy. Type I IFN activates immune cells boosts antigen presentation and controls proliferation. In addition, type I IFN increases tumour cell sensitivity to the blockade. Combining the two therapies increases tumoral T cell infiltration and activation within tumours, and stimulate the generation of memory T cells, leading to prolonged patient survival. However, limitations include heterogeneous responses, the need for biomarkers to predict and monitor outcomes, and adverse effects and toxicity. Although treatment resistance remains an obstacle, the combined therapeutic efficacy of IFNα/β and PD-1/PD-L1 blockade demonstrated considerable benefits across a spectrum of cancer types, notably in melanoma. Overall, the phases I and II clinical trials have demonstrated safety and efficiency. In future, further investigations in clinical trials phases III and IV are essential to compare this combinatorial treatment with standard treatment and assess long-term side effects in patients.